Unexpected effects of systemic steroids on the CRSwNP proteome: is protein upregulation more important than inhibition?. Issue 3 (5th February 2020) - Workman, Alan D.; Miyake, Michelle M.; Nocera, Angela L.; Mueller, Sarina K.; Finn, Kristen; Otu, Hasan H.; Libermann, Towia A.; Bleier, Benjamin S.
Abstract : Background: Oral steroids, traditionally thought of as immunosuppressive agents that are broad in their immunomodulatory effects, are a mainstay of treatment to reduce disease burden in chronic rhinosinusitis with nasal polyps (CRSwNP). The purpose of this study was to determine how differentially expressed proteins in CRSwNP are affected by oral steroid therapy. Methods: Matched exosomal proteomic arrays were quantified using aptamer‐based methods in systemic steroid‐naive CRSwNP patients before and after a standardized oral prednisone course (n = 12). Previously identified differentially expressed proteins in CRSwNP patients were compared to determine the effect of steroids on expression. Fisher's exact test and t test were applied to normalized protein expression profiles to determine significance. Results: Of 18 proteins previously identified to be highly underexpressed in CRSwNP, 16 (89%) had an average increase after systemic steroid treatment ( p < 0.05). Lactoperoxidase, initially present at 9‐fold lower concentrations in CRSwNP subjects, increased by 209% after steroid treatment. A similar trend was observed with other proteins of interest, including platelet factor 4 and C‐C motif ligand 28. The converse of this steroid effect was not true; of the 53 proteins that are highly overexpressed in CRSwNP, only 22 (42%) decreased in quantity with steroid use. Conclusion: Proteomic analysis of differentially expressed proteins in CRSwNP demonstrates that systemic steroids cause almost uniform upregulation of transcriptionally decreased proteins, whereas the effects of steroids on transcriptionally increased proteins are more heterogeneous. Thus, proteomic analysis may be an effective tool to understand specific therapeutic benefits of steroid use in polyp disease and to create more targeted treatments.